2011
DOI: 10.1177/0093650211405649
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Activism in Response to the Influence of Political Parody Videos on YouTube

Abstract: Grounded in scholarship on both the perceptual and behavioral components of the thirdperson effect, the present experimental study examined the effects of perceived impact of political parody videos on self and on others, by varying the perceived intent of the video producer and perceived level of exposure. Building on previous research on the behavioral consequences of such presumed influence, we tested a hierarchical regression model to show how perceived influence on others predicted individuals' willingnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 41 publications
0
69
3
2
Order By: Relevance
“…Smith & Duggan, 2012). It should therefore come as no surprise that scholars have begun to explore the impact of exposure to these parody videos on viewer perceptions and political engagement (Becker, 2014;Lim & Golan, 2011;Tryon, 2008). Previous empirical research has suggested that exposure to politically oriented usergenerated YouTube content can impact evaluations of target politicians' credibility and favorability but has failed to offer evidence of a relationship between exposure to political content and feelings of political cynicism or efficacy (Rill & Cardiel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Smith & Duggan, 2012). It should therefore come as no surprise that scholars have begun to explore the impact of exposure to these parody videos on viewer perceptions and political engagement (Becker, 2014;Lim & Golan, 2011;Tryon, 2008). Previous empirical research has suggested that exposure to politically oriented usergenerated YouTube content can impact evaluations of target politicians' credibility and favorability but has failed to offer evidence of a relationship between exposure to political content and feelings of political cynicism or efficacy (Rill & Cardiel, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous studies, the perception of media influences on other people can result in increased political participation (e.g., Lim & Golan, 2011;Rojas, 2010). In the present study, this relation was examined in the context of an election.…”
Section: Discussionmentioning
confidence: 56%
“…One exception to this is a study by Lim and Golan (2011) that shows that the stronger the influence of political YouTube videos was thought to be on others, the more willing the respondents were to critically comment on them or to upload their own videos professing the opposite political tendency. Bernhard and Dohle (2013) also took online media into account in a study on the context of the dispute about a public construction project in Germany.…”
Section: Corrective Actions As Consequences Of Perceptions In the Conmentioning
confidence: 99%
See 2 more Smart Citations